Employment and Recidivism on Federal Probation: A Comparison between Whites and Native Americans under Supervision - Tuttle, James (Journal of crime and justice, 2024)
Despite extensive research on the impact of employment on offending and recidivism, little is known about how it influences the recidivism of Native Americans. In this study, we compare the likelihood of recidivism by race, examining the difference between Whites and Native Americans on Federal Probation in a Western state. Compared to Whites, Native Americans have a higher risk of recidivism and are less likely to be employed at the beginning of probation supervision. Ultimately, employment fully mediates the impact of race on recidivism. We discuss our findings within the broader context of systemic barriers to employment for Native Americans.